Estudio correlacional tuberculosis vs sindrome de inmunodeficiencia adquirida (Sida) - Jessica Thalia, Salazar Chiliquinga (2020)
Background: The OMS mentions that approximately 1000 people infected with the human immunodeficiency virus (HIV) die every day from tuberculosis worldwide. However, in Ecuador there has been a slight decrease in tuberculosis cases in patients immunosuppressed by HIV due to compliance with the Legal Norm in the country. General Objective: To determine the correlation between tuberculosis and HIV positive patients in the Infectiology area of the Carlos Andrade Marín Hospital during 2019 through the collection and analysis that allow us to know the frequency of these pathologies, in order to demonstrate the effectiveness of the strategies created by the health system. Material and methods: this research is a cross-sectional retrospective study, in which data collected from patients hospitalized for Human Immunodeficiency Virus and Tuberculosis, it should be noted that tuberculosis is an opportunistic disease that is present in immunosuppressed patients. Results: the population consists of 200 HIV-positive patients treated in the Infectiology area, from this population a sample of 42 patients who also presented tuberculosis extracted. Among patients with HIV positive and tuberculosis, 43% are older adults, 35% are male, and pulmonary tuberculosis is the predominant disease Conclusions: 200 patients diagnosed with HIV, 42 have Tuberculosis coinfection, which translates as a minority and it understood that the established health strategies are giving good results.